2023
DOI: 10.3390/ijms24065603
|View full text |Cite
|
Sign up to set email alerts
|

A Kaleidoscope of Keratin Gene Expression and the Mosaic of Its Regulatory Mechanisms

Abstract: Keratins are a family of intermediate filament-forming proteins highly specific to epithelial cells. A combination of expressed keratin genes is a defining property of the epithelium belonging to a certain type, organ/tissue, cell differentiation potential, and at normal or pathological conditions. In a variety of processes such as differentiation and maturation, as well as during acute or chronic injury and malignant transformation, keratin expression undergoes switching: an initial keratin profile changes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 293 publications
(231 reference statements)
0
4
0
Order By: Relevance
“…Worthy of note, the expression of cytokeratins differs considering the condition of the tissue. Indeed, these markers can be activated as a result of wound healing or inflammation [19][20][21], and their expression can change considerably due to pathologic processes, including genetic conditions such as aniridia [60,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worthy of note, the expression of cytokeratins differs considering the condition of the tissue. Indeed, these markers can be activated as a result of wound healing or inflammation [19][20][21], and their expression can change considerably due to pathologic processes, including genetic conditions such as aniridia [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Within this scope, cytokeratins have been widely employed. However, several concerns remain about their expression change in specific conditions, such as in a proliferating/ wound-healing state [19][20][21]. Our previous work suggested SOX2 as a univocal marker to distinguish the oral mucosa from corneal and conjunctival cells based on an unbiased gene array transcriptome profile analysis of single cells derived from different regions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Their descendants move downward and repopulate the hair matrix in the hair bulb, which gives rise to the hair shaft and inner root sheath. The HF epithelial compartment is one of the most multifaceted and specialized populations between the epithelia [ 120 ]. The mesenchymal part of an HF represents the dermal papilla that is embedded in a hair bulb and connective tissue sheath surrounding the hair follicle [ 121 ].…”
Section: Actual Questions From Mouse To Human Skinmentioning
confidence: 99%
“…Among the homeostasis maintaining epithelial components keratins are crucial cytoskeletal proteins and their expression is changed in colonic stress conditions 21 . Further, keratins have been shown to react to stress in other tissues and upregulation of several keratin genes are associated with cancer progression 22 . K7 is found to be expressed in UC-related neoplasms 23 , 24 , and we previously found that K7, not expressed in healthy colonic epithelium, is significantly upregulated in IBD and the highest focal K7 positive cell levels were found to be associated with the most severe epithelial damage and the samples with granulomas close to epithelium had increased number of K7 positive cells 17 .…”
Section: Introductionmentioning
confidence: 99%